Trodden paths and untrodden lanes: Tongan students' readings across texts - Maka, Lia L. (1996)
Using poststructuralist notions of `texts', `textuality ', `discourse', `subjectivity' and `knowledge, this study explores the kinds of meaning links and the location of these links as made by a group of 14-16 year olds Tongan students when they read a range of literary and informative texts (poems, short stories, advertisements, cartoon).